(untitled) (Proceedings of Southern Federal University. Philology, 2019)
Ilya N. Chernyshev (Rostov-on-Don, Russian Federation) The article researches aspects of functioning of images, connected with body motion in the novel «Dream of Fair to Middling Women», written by Samuel Beckett. The phenomenological approach used in the analysis allows to clarify the artistic concept of the early work of the writer, who successively manifest his perception of the world through images connected with motion or absence of motion. Young writer’s reflections on the theme of impossibility of successful communication between the outer world and the protagonist, who claims his right on freedom from the scheduled cyclicity of being, are also expressed through the images of motion, by which the plot composition and portraits of characters are described. Key words: motion, body, Beckett, system of images, cyclicity. DOI 10.23683/1995-0640-2019-3-164-171